Soundspace VR: spatial navigation using sound in virtual reality - Fialho, Luís Miguel da Costa (2022)
Prior research reveals that spatial navigation skills rely mostly in visual sensory abilities, but the study of how spatial processing operates in the absence of visual information is still incomplete. Therefore, a spatial navigation task in virtual reality using auditory cues was developed to study navigational strategies in blindfolded sighted individuals. Twenty healthy adult participants were recruited. The task consisted of a VR scene, in which participants were asked to localize a sound source and move to the target without visual information throughout the entire task. Task difficulty was manipulated by route length and complexity in three different difficulty levels repeated in two different trials. The first trial (learning) consisted of moving to the sound source and then returning to the starting point. The second trial (retrieval) consisted of the same task without the sound source but with auditory cues from obstacles to test spatial learning. Performance was assessed from behavioral measures of execution time, obstacle collisions, and prompts during the task execution. These variables were compared to established neuropsychological instruments for global cognition (Montreal Cognitive Assessment) and memory abilities (Wechsler Memory Scale-R). The results suggested that difficulty level affected navigation performance in both trials. Navigation performance was better in the retrieval trial, but both learning and retrieval trials were explained by global cognitive functioning. These data suggested the Soundspace VR as being effective to study spatial navigation in the absence of visual information and highlight the importance of auditory information from spatial sound cues for spatial navigation and spatial learning.